2002
DOI: 10.1242/dev.00150
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/Tcf-regulated transcription prior to the midblastula transition

Abstract: Following fertilization, the zygotic genome in many organisms is quiescent until the midblastula transition (MBT), when large-scale transcription begins. In Xenopus embryos, for example, transcription is believed to be repressed until the twelfth cell division. Thus, although dorsal-ventral patterning begins during the first cell cycle, little attention has been given to transcriptional regulation in pre-MBT development. We present evidence that regulated transcription begins during early cleavage stages and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(173 citation statements)
references
References 43 publications
7
165
1
Order By: Relevance
“…Instead, maternal JNK has an unusual pattern of temporal activity that starts from oocyte maturation and ends at early gastrulation, coinciding with the formation of dorsal structures. Thus, although a confined and low level of nuclear ␤-catenin specifies the future dorsal axis in early Xenopus embryos (37), the sustained high level of maternal JNK activity may act as a gatekeeper to prevent promiscuous nuclear ␤-catenin accumulation that could lead to hyperdorsalization. Taken together, these results suggest that Ca 2ϩ ͞CamKII͞NFAT and Dsh͞JNK provide spatial and temporal regulation of the canonical Wnt signaling, respectively, for axis formation in Xenopus embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, maternal JNK has an unusual pattern of temporal activity that starts from oocyte maturation and ends at early gastrulation, coinciding with the formation of dorsal structures. Thus, although a confined and low level of nuclear ␤-catenin specifies the future dorsal axis in early Xenopus embryos (37), the sustained high level of maternal JNK activity may act as a gatekeeper to prevent promiscuous nuclear ␤-catenin accumulation that could lead to hyperdorsalization. Taken together, these results suggest that Ca 2ϩ ͞CamKII͞NFAT and Dsh͞JNK provide spatial and temporal regulation of the canonical Wnt signaling, respectively, for axis formation in Xenopus embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Early zygotic transcription of a gene has been thought to be rare, but examples have been characterized in Xenopus (Yang et al, 2002). Recently, a set of over one hundred zebrafish genes that are transcribed prior to the mid-blastula transition were identified by microarray analysis (Mathavan et al, 2005), although chch was not identified in this screen.…”
Section: Zebrafish Chch Is Expressed Prior To the Mbtmentioning
confidence: 99%
“…Early zygotic transcription of a gene has been thought to be rare, but examples have been characterized in Xenopus (Yang et al, 2002). Recently, a set of over one hundred zebrafish At sphere and shield stages, chch is widely expressed but some cells express higher levels of chch ( fig.…”
Section: Zebrafish Chch Is Expressed Prior To the Mbtmentioning
confidence: 99%
“…However, no difference of the E2F mobility during development seems to preclude this hypothesis. Thirdly, basic transcriptional machinery may be activated at or around MBT, which seems most feasible, but a recent report suggests that some transcription of mRNA from zygotic genome before MBT was active (Yang et al, 2002), although the detailed analysis remains to be done.…”
Section: Discussionmentioning
confidence: 99%